Caracterização fenológica, adubação e potencial agronômico de espécies de pitaia - Silva, Luciana Sabini da (2023)
Pitaya is an exotic fruit that is expanding in Brazilian markets, generating growing commercial cultivation. The objective of this work was to evaluate the phenology, agronomic potential and fruit characteristics of pitaya species submitted to different fertilizations. The experiments were conducted on the farm at the Experimental Farm “Prof. Antônio Carlos dos Santos Pessoa”, in Marechal Cândido Rondon/PR. The experimental design was in randomized blocks, factorial scheme 5 x 2 [four top dressing fertilizations (T1 = 14 kg of tanned bovine manure, T2 = 2 kg of chicken manure, T3 = 7 kg of tanned bovine manure + 1 kg of bedding). tanned aviary, T4 = mineral fertilization (NPK) and T5= zero fertilization/control) x two dragon fruit species (Hylocereus undatus, Hylocereus polyrhizus)]. The evaluations were carried out in the 2019/20 and 2020/21 harvests. In experiment I, the evaluation of phenology began 21 months after transplanting the seedlings and was carried out daily from the appearance of the first flower bud in the orchard, in addition, phytotechnical parameters were evaluated. In experiment II, the growth rate was calculated using the TCA method (absolute growth rate). Growth measurements were: plant height, number of cladodes in the plant, number of shoots at the base, length of shoots, fresh mass of shoots. And in experiment III, the chemical characteristics of the fruits were evaluated: phenolic compounds, antioxidant activity (DPPH), ascorbic acid content (vitamin C), total acidity and pH. The duration of the phenological cycle of pitaya species is influenced by annual climatic conditions and the type of fertilization. The reproductive cycle of the crop takes an average of 30 days. The greatest period of growth of the species occurs from August to November. Fertilization with poultry litter and cattle manure is recommended in February, August and November. The fruits of the studied species underwent changes in chemical characteristics depending on the source of fertilization, with H. undatus being the species with the highest content of phenolic compounds under the studied conditions.